2018
DOI: 10.1002/cctc.201800076
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Hybrid Homogeneous–Heterogeneous Catalysis in a Pt/Au Heterobimetallic System

Abstract: We report here our efforts towards understanding the catalytic species involved in a novel Pt/Au heterobimetallic system capable of efficiently catalysing the tandem cyclisation/C−X coupling reaction of heteroarylallenes with C‐ and N‐based nucleophiles. Our results confirm that homogeneous Au‐catalysis is involved at the beginning of the reaction to generate an intermediate that enters the second catalytic cycle in which hybrid homogeneous–heterogeneous catalysis by [Pt–Au] clusters could be responsible for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…In the context of allene chemistry, Au–Pd dual catalysis has been reported in the reaction of allenoates to form butenolides . We have recently reported a dual Au–Pt strategy for the reaction of heteroarylallenes in the reaction with heteroaromatic nucleophiles, showing unprecedented reactivity not observed previously with single catalysis strategies …”
mentioning
confidence: 84%
“…In the context of allene chemistry, Au–Pd dual catalysis has been reported in the reaction of allenoates to form butenolides . We have recently reported a dual Au–Pt strategy for the reaction of heteroarylallenes in the reaction with heteroaromatic nucleophiles, showing unprecedented reactivity not observed previously with single catalysis strategies …”
mentioning
confidence: 84%
“…Detailed investigations into this transformation suggested that the more efficient bimetallic strategy vs. the single catalyst methodology was due to synergic cooperation between soluble gold-platinum clusters in equilibrium with heterogeneous goldplatinum particles generated in situ, reporting, therefore, the first example of hybrid homo-heterogeneous catalysis in a bimetallic system. [75] Tandem reactions involving untethered indoles and allenes are increasingly appearing in the literature and most of the examples are from the last 3 years. In most of them, the intermolecular reaction occurs first to give intermediates that undergo intramolecular processes.…”
Section: Tandem Intra-inter or Inter-intramolecular Reactionsmentioning
confidence: 99%
“…Detailed investigations into this transformation suggested that the more efficient bimetallic strategy vs. the single catalyst methodology was due to synergic cooperation between soluble gold‐platinum clusters in equilibrium with heterogeneous gold‐platinum particles generated in situ, reporting, therefore, the first example of hybrid homo‐heterogeneous catalysis in a bimetallic system. [ 75 ]…”
Section: Tandem Reactionsmentioning
confidence: 99%
“…An upward trend in the publication of binuclear complexes has been visible over the past decade. Meanwhile, investigations of heterobimetallic Pt–Au systems show a leap forward in different categories, including structural, photoluminescence, catalysis, , and therapeutic. Although heterobimetallic Pt–Au systems are still in the early stages of development, their reasonable biological features make them a viable and highly potent class of cancer chemotherapeutic agents.…”
Section: Introductionmentioning
confidence: 99%